Isolation and antibacterial screening of marine heterotrophic bacteria from Makassar Strait, Indonesia - De Fretes, Charlie Ester; Pesilette, Rosmi Nuslah; Sohilait, Mario Rowan; Yanubi, Dorthea; Ririhatuela, Florensia Claudya Thalia; Satwika, Dhira (Penerbit Universiti Kebangsaan Malaysia, 2024)
The biological potential of microorganisms in Indonesian waters has yet to be widely reported despite their high diversity. This research aimed to isolate bacteria from seawater and seabed sediments in Makassar Strait and then screen their potential antibacterial abilities. Subsequently, we tried to determine the bioactive compound content of the bacterial extracts. We purified 15 bacterial isolates and based on a 16S rRNA analysis, we found that these bacteria represented three phyla, namely Actinobacteria, Firmicutes, and Proteobacteria. All the isolates were found to have antibacterial capabilities, while 2 isolates showed positive results for inhibiting the growth of the pathogens tested. Molecular analysis studies provided information that the two isolates which were Bacillus sp., namely B. stratosphericus TR4 and B. thuringiensis TR13, were detected to have non-ribosomal peptide synthetase (NRPS) genes, which are thought to contribute to their antibacterial potential. Compounds from the imidazole group, quinolone ester derivatives, steroid derivatives, and acetamide derivatives were found in the extracts of both strains. Further research needs to be conducted to better understand each compound’s antibacterial mechanisms and possible interesting bioactive properties.